Psychiatric Symptoms of Children and Adolescents With Mitochondrial Disorders: A Descriptive Case Series - Riquin, Elise; Le Nerzé, Thomas; Pasquini, Natwin; Barth, Magalie; Prouteau, Clément; Colin, Estelle; Amati Bonneau, Patrizia; Procaccio, Vincent; Van Bogaert, Patrick; Duverger, Philippe; Bonneau, Dominique; Roy, Arnaud (Frontiers in Psychiatry, 2021)
Background: Mitochondrial disorders (MD) are a group of clinically heterogeneous genetic disorders resulting from dysfunction of the mitochondrial respiratory chain. Cognitive impairment is a common feature in adults with MD and psychiatric symptoms are associated with MD in up to 70% of the adult population. The aim of this study is to describe the psychiatric profile in children and adolescents with MD by focusing on the description of psychiatric symptoms. Methods: A cohort of 12 children and adolescents was prospectively recruited between February 2019 and February 2020 in the Reference Center for Mitochondrial Disorders of Angers (France). Participants and their parents completed an anamnestic form to provide socio-demographic data and completed the Global Assessment of Functioning scale, the Brief Psychiatric Rating Scale, the Child Depression Inventory, the Revised Children's Manifest Anxiety Scale, and the Conner’s Rating Scale to evaluate the inattention/hyperactivity symptoms as well as the Quality of Life scale. Results: Four children (33.3%) were diagnosed with depressive symptoms. With regarding to anxiety, 6 children (50%) reported anxiety issues during the psychiatric interview and 3 children (25%) were suffering from anxiety according to the RCMAS scale. Compared to other children with chronic illnesses, the individuals in our cohort reported a lower overall quality of life score and lower scores in physical and social subscales. Conclusion: Our study shows that MD can lead to psychiatric disorders in children and adolescents, in particular anxiety and depression, as well as poor quality of life. This highlights the need for regular psychiatric assessments in individuals with developing brains, such as children and adolescents. We do not, however, have data regarding the neuropsychological profile of this population.